2019
DOI: 10.1155/2019/3706143
|View full text |Cite
|
Sign up to set email alerts
|

Contributing to Global Health: Development of a Consensus-Based Whole Systems Research Strategy for Anthroposophic Medicine

Abstract: Background Whole medicine and health systems like traditional and complementary medicine systems (T&CM) are part of healthcare around the world. One key feature of T&CM is its focus on patient-centered and multimodal care and the integration of intercultural perspectives in a wide range of settings. It may contribute to good health and well being for people as part of the Sustainable Development Goals of the United Nations. The authentic, rigorous, and fair evaluation of such a medical system, with its inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 125 publications
2
7
0
1
Order By: Relevance
“…f moderation also focused on the work of Mahmood and Tayib (2020), which found that key elements to building a healing environment: (1) Appearance, (2) Privacy, and (3) control. This is consistent with methods such as Kienle et al (2019), excluding cal medicine is also derived from both consensus-based and traditional and y medicine (T&CM) programs:…”
Section: Balancing Strategiessupporting
confidence: 79%
See 1 more Smart Citation
“…f moderation also focused on the work of Mahmood and Tayib (2020), which found that key elements to building a healing environment: (1) Appearance, (2) Privacy, and (3) control. This is consistent with methods such as Kienle et al (2019), excluding cal medicine is also derived from both consensus-based and traditional and y medicine (T&CM) programs:…”
Section: Balancing Strategiessupporting
confidence: 79%
“…The perspective described above is compatible with an approach known as anthroposophical medicine, which also approaches human health from a systemic or holistic perspective. More specifically, the anthroposophical concept, conceives of the human organism as a manifestation of multiple elements including physical forces, formative growth forces, and an interacting anima, or soul, as outlined by (Sparby, 2020) (Kienle et al 2019). From this perspective, human existence can be thought of as a kind of system of systems, complete with sensory, motor, nervous, and circulatory systems, and, finally, with an additional Geist, or spirit, involved in individual expression and reflection.…”
Section: Introductionmentioning
confidence: 99%
“…51,57,126 A whole systemsbased research strategy for anthroposophic medicine has recently been proposed and published. 305 6. Critics charge anthroposophic physicians with medical neglect, improper diagnosis, and inappropriate and failed treatment.…”
Section: The Brain and Consciousnessmentioning
confidence: 99%
“…While not a recognized qualification for physicians, anthroposophic medicine is commonly used by German physicians. This medical system is based on a specific organismic concept and uses drugs derived from herbal, mineral, and animal sources, eurythmy (a specific movement therapy), art therapy, rhythmical massage, and lifestyle recommendations [ 18 ] (Supplementary digital file 2). No formal qualification is mandatory to practice IM in Germany.…”
Section: Introductionmentioning
confidence: 99%